Evaluación de la incidencia de la fotoestimulación en la fermentación del mosto cervecero a escala laboratorio (2016)
The present project based a comparative analysis of sugar substrate consume, cell growing and alcohol production of yeast Saccharomyces cerevisiae type Safale S-04, at culture medium beer must during the fermentation of 1 L of craft beer type American Pale Ale at laboratory level. The photo- fermentation process was performed in a fermenter type photobioreactor whit volume of 1 L. The photobioreactor was built in transparent acrylic, dissuaded, and adapted to fit to an LED light source model, which obtained an average illuminance of 65000 Lux. The fermentation in the absence of light was carried out in a glass bottle of boron-silicate whit a capacity of one liter.